Tensile mechanical properties, deformation mechanisms, fatigue behaviour and fatigue life of 316H austenitic stainless steel: Effects of grain size. Issue 2 (11th November 2020) - Zhao, Lei; Qi, Xueyan; Xu, Lianyong; Han, Yongdian; Jing, Hongyang; Song, Kai
Abstract: To explore the effect of grain size on the tensile behaviour, symmetrical strain control fatigue behaviour and ratcheting fatigue behaviour of the new austenitic steel 316H, a series of tensile tests, symmetrical strain control fatigue tests and ratcheting fatigue tests were conducted at 25°C within an average grain size range from 14 to 122 μm. The average dislocation free path, forest dislocation density and mobile dislocation density of 316H steel with different grain sizes under tension were obtained. Moreover, the decrease of grain size led to saturation of mobile dislocations at lower strains. The decrease of grain size led to the increase of the cyclic stress and affected softening and secondary hardening process. In addition, under the same stress control conditions, the reduction in grain size caused a reduction in ratcheting strain under the same cycle. The grain refinement of 316H steel contributed to the improvement of ratcheting fatigue life.